Genome‐wide identification and expression analysis of SlRR genes in response to abiotic stress in tomato. (30th December 2022) - Liu, H.; Chen, R.; Li, H.; Lin, J.; Wang, Y.; Han, M.; Wang, T.; Wang, H.; Chen, Q.; Chen, F.; Chu, P.; Liang, C.; et al.
Abstract: The cytokinin two‐component signal transduction system (TCS) is involved in many biological processes, including hormone signal transduction and plant growth regulation. Although cytokinin TCS has been well characterized in Arabidopsis thaliana, its role in tomato remains elusive. In this study, we characterized the diversity and function of response regulator ( RR ) genes, a critical component of TCS, in tomato. In total, we identified 31 RR genes in the tomato genome. These SlRR genes were classified into three subgroups (type‐A, type‐B and type‐C). Various stress‐responsive cis ‐elements were present in the tomato RR gene promoters. Their expression responses under pesticide treatment were evaluated by transcriptome analysis. Their expression under heat, cold, ABA, salinity and NaHCO3 treatments was further investigated by qRT‐PCR and complemented with the available transcription data under these treatments. Specifically, SlRR13 expression was significantly upregulated under salinity, drought, cold and pesticide stress and was downregulated under ABA treatment. SlRR23 expression was induced under salt treatment, while the transcription level of SlRR1 was increased under cold and decreased under salt stress. We also found that GATA transcription factors played a significant role in the regulation of SlRR genes. Based on our results, tomato SlRR genes are involved in responses to abiotic stress in tomato and could be implemented in molecular breeding approaches to increase resistance of tomato to environmental stresses. Abstract : We identified 31 RR genes in tomato which were involved in response to abiotic stress and could be implemented in molecular breeding approaches to increase tomato environmental resistance.